DIVERSITY OF MICROBIAL STRAINS INVOLVED IN COCOA FERMENTATION FROM SUD-COMOÉ (COTE D’IVOIRE) BASED ON BIOCHEMICAL PROPERTIES - Kouame, Liliane M.; Goualie, Bernadette G.; Adom, Jacques N.; Koua, Gisele; Ouattara, Honore G.; Doue, Ginette; Niamke, Sebastien L. (European Scientific Journal, ESJ, 2015)
The cocoa pulp fermentation is one of keys step for obtaining a quality chocolate. However, microflora involved in this process is complex and variable that leads to inconsistent production efficiency on cocoa quality. Here we investigate the diversity of microflora implicated in Sud-Comoé (area of Côte d’Ivoire) cocoa fermentation based on their biochemical properties. During fermentation, yeasts, Lactic Acid Bacteria (LAB) and Acetic Acid Bacteria (AAB) reached maximum load at 36, 24 and 72 h respectively and decreased rapidly while the rate of Bacillus load increased throughout the fermentative process to reach a peak at 144 h. Among the Bacillus strains, 62.22, 87.5 and 33.7 % were able to produce pectinolytic enzymes, acid and citrate lyase respectively. Concerning yeasts strains, 25.43 % showed pectinolytic enzymes production capacity and all of these isolates were able to ferment glucose and fructose while 52 % were able to produce gas from sucrose. Population of LAB was predominant by homofermentative group with proportion at 85.96 % while AAB were dominated by genera Acetobacter with 88.78 %. Therefore, this study shows the diversity of biochemical properties of tested microbial strains indicating a diversity of microbiota involved in Sud-Comoé cocoa fermentation.